Fluid balance and carbohydrate intake of elite female soccer players during training and competition - Tarnowski, C. A.; Rollo, I.; Carter, J. M.; Lizarraga-Dallo, M. A.; Porta Oliva, M.; Clifford, T.; James, L. J.; Randell, R. K. (Nutrients, 2022)
This study examined sweat rate, sweat sodium concentration [Na+], and ad-libitum carbohydrate and fluid intakes in elite female soccer players during training (n = 19) and a match (n = 8); eight completed both for comparisons. Body mass (kg) was obtained before and after exercise to calculate sweat rate. The sweat [Na+] was determined from absorbent patches on the thigh or back. Sweat rate, percentage body mass change, and sweat [Na+] for 19 players during training were 0.47 ± 0.19 L·h-1, +0.19 ± 0.65%, and 28 ± 10 mmol·L-1, respectively. Sweat rate was higher during a match (0.98 ± 0.34 L·h-1) versus training (0.49 ± 0.26 L·h-1, p = 0.007). Body mass losses were greater post-match (-1.12 ± 0.86%) than training (+0.29 ± 0.34%, p = 0.003). Sweat [Na+] was similar for training (29 ± 9 mmol·L-1) and a match (35 ± 9 mmol·L-1) (p = 0.215). There were no differences in match versus training carbohydrate intakes (2.0 ± 2.3 g·h-1, 0.9 ± 1.5 g·h-1, respectively, p = 0.219) or fluid intakes (0.71 ± 0.30 L·h-1, 0.53 ± 0.21 L·h-1, respectively, p = 0.114). In conclusion, female soccer players` sweat rates were higher during a match than during training, and carbohydrate intakes were below recommendations for matches and training.